Abnormal Conduction Zone Detected by Isochronal Late Activation Mapping Accurately Identifies the Potential Atrial Substrate and Predicts the Atrial Fibrillation Ablation Outcome After Pulmonary Vein Isolation. (23rd January 2023) - Kuo, Ming-Jen; Ton, An Nu-Khanh; Lo, Li-Wei; Lin, Yenn-Jiang; Chang, Shih-Lin; Hu, Yu-Feng; Chung, Fa-Po; Tuan, Ta-Chuan; Chao, Tze-Fan; Liao, Jo-Nan; Chang, Ting-Yung; Lin, Chin-Yu; et al.
Abstract : Background: The presence of abnormal substrate of left atrium is a predictor of atrial fibrillation (AF) recurrence after pulmonary vein isolation. We aimed to investigate the isochronal late activation mapping to access the abnormal conduction velocity for predicting AF ablation outcome. Methods: Forty-five paroxysmal AF patients (30 males, 57.8±8.7 years old) who underwent pulmonary vein isolation were enrolled. Isochronal late activation mapping was retrospectively constructed with 2 different windows of interest: from onset of P wave to onset of QRS wave on surface electrocardiography (W1) and 74 ms tracking back from the end of P wave (W2). Deceleration zone was defined as regions with 3 isochrones (DZa) or ≥4 isochrones (DZb) within a 1 cm radius on the isochronal late activation mapping, and the estimated conduction velocity (ECV) are 0.27 m/s and <0.20 m/s for DZa and DZb, respectively in W2. The distribution of deceleration zone was compared with the location of low-voltage zone (bipolar voltage ≤0.5 mV). Any recurrence of atrial arrhythmias was defined as the primary end point during follow ups after a 3-month blanking period. Results: Pulmonary vein isolation was performed in all patients, and there were 2 patients (4.4%) received additional extrapulmonary vein ablation. After a mean follow-up of 12.7±4.5 months, recurrence of AF occurred in 14 patients (31.1%). Patients with the presence of DZb in W2 had higher AF recurrence (Kaplan-Meier event rate estimates: HR, 9.41 [95% CI, 2.61–33.90]; log-rank P <0.0001). There were 52.6% of the DZb locations in W2 comparable to the distributions of low-voltage zone and 47.4% DZb were distributed in the area without low-voltage zone. Conclusions: Deceleration zone detected by isochronal late activation mapping represents a critical AF substrate, it accurately predicts the AF recurrence following ablation in patients with paroxysmal AF.